Chitosan/poly (acrylic acid) based fiber-optic surface plasmon resonance sensor for Cu2+ ions detection - Ding, Zhe-Wen (2021)
A novel fiber-optic surface plasmon resonance sensor for detection of Cu 2+ ions in an aquatic environment is proposed and experimentally demonstrated. The proposed sensor is fabricated by splicing no-core fiber between multimode fibers and then functionalizing the sensor surface with gold film and chitosan (CS)/poly(acrylic acid) (PAA) bilayers. The gold film is used to stimulate surface plasmon waves and make the sensor sensitive to changes in refractive index induced by Cu 2+ ions absorption on the CS/PAA bilayers. The proposed sensor has a linear relationship between the wavelength shifts and the concentrations of Cu 2+ ions from 0.2 to 50 μM and 50 to 500 μM, respectively. It is also observed that the sensor's performance is better at low concentrations, and its sensitivity decreases with the increasing concentration. Moreover, we find the proposed sensor can express the self-assembly process between CS and PAA clearly, which shows us a new and easy way to investigate the polyelectrolyte self-assembling.